ANALISIS PEMBIAYAAN MUDHAR1ABAH DAN MUSYARAKAH TERHADAP PENDAPATAN BANK BNI SYARIAH - Zahra Zetira; Wirman . (Jurnal Mirai Management, 2021)
This study aims to analyze the mudharabah and musyarakah financing on the income of BNI Syariah Bank by using the data sample in 2020 as a reference in making conclusions regarding the income obtained by BNI Syariah Bank. This analysis uses a quantitative descriptive analysis method on transparency data presented by BNI Syariah Bank. The results of this study indicate that the mudharabah and musyarakah financing at BNI Syariah Bank are in good category and have a significant effect on the income of BNI Syariah Bank.